State Security of Socialist Republic of Croatia and events in Poland 1980-1982 - Barić, Nikica (Balcanica Posnaniensia. Acta et studia, 2021)
The Socialist Republic of Croatia, as one of republics of the Socialist Federative Republic of Yugoslavia, possessed its State Security Service (Služba državne sigurnosti, SDS), equivalent to similar political security services in other communist states. At the Yugoslav level there was also the Federal State Security Service. The State Security of Croatia dealt with both internal and external threats to the communist system and gathered intelligence information. In the early 1980s the State Security of Croatia gathered sizeable amount of information on the events connected with activities of „Solidarity” in the People’s Republic of Poland and the crisis that ultimately led to the imposition of state of war in Poland, as well as reaction to these events in Croatia. The main aim of this paper is to present State Security reports about with Poland in the period between 1980 and 1982.